2011
DOI: 10.2320/matertrans.l-mz201110
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Unidirectional Carbon Fiber Preform for Aluminium Matrix Composites

Abstract: The unidirectional carbon fiber (CF) preform for carbon fiber reinforced aluminium (CF/Al) composites has been investigated in terms of the fabrication condition and the strength property. The CF preform which consists of CFs and Cu particles was fabricated by spark plasma sintering (SPS) process with different fabrication temperatures. In order to determine the infiltration pressure of molten Al to the CF preform, the compression test was performed to the CF preform. The unidirectional CF preform by SPS proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Moreover, the full width at half maximum (FWHM) of (002) deceased from 5.280°to 1.528°. The decrease in FWHM of (002) indicated that the distance between carbon aggerates decreased, 14) resulting in higher phonon velocity in the porous VGCF/ MP. 15) To investigate the elemental distribution of VGCF/MP/Al composite (MP and 0.5 vol% VGCFs, after carbonization), EPMA was carried out in the same area as Fig.…”
Section: Characterization Of Microstructure Porosity and Thermal Conductivitymentioning
confidence: 99%
“…Moreover, the full width at half maximum (FWHM) of (002) deceased from 5.280°to 1.528°. The decrease in FWHM of (002) indicated that the distance between carbon aggerates decreased, 14) resulting in higher phonon velocity in the porous VGCF/ MP. 15) To investigate the elemental distribution of VGCF/MP/Al composite (MP and 0.5 vol% VGCFs, after carbonization), EPMA was carried out in the same area as Fig.…”
Section: Characterization Of Microstructure Porosity and Thermal Conductivitymentioning
confidence: 99%
“…세라믹/금속 복합재료에서 W a 는 금속과 세라믹 계면에서의 상호작용의 강도를 수치화 한 것이며 이는 세라믹/금속 복합재료의 기계적 특성을 모 델링할 때 항상 고려하는 부분이다 [7]. 현재 탄소섬유/알루미늄 복합재료 제조를 위해 많이 연 구되고 있는 방법으로는 squeeze casting법이나 infiltration 법 등이 있다 [8][9][10][11][12] …”
Section: 서 론unclassified
“…Although the MMCs are very attractive materials for automobile industry, the raw materials and its manufacturing method are not cost effective compared with the conventional materials and its manufacturing system. However, the low-pressure infiltration method [5][6][7] is one of the useful casting methods for MMCs, due to apply low-pressure in comparison with high pressure casting such as die casting and squeeze casting. 8,9 Furthermore, low pressure is able to produce complex/ large shape and accomplish high cost-performance.…”
Section: Introductionmentioning
confidence: 99%